MODEL PENGEMBANGAN PERMAINAN SEPAK BOLA KAKI DAN TANGAN DALAM PEMBELAJARAN PENDIDIKAN JASMANI DAN KESEHATAN BAGI SISWA KELAS V DI SDN 01 BEJI (Department of Physical Education, Sport, Health and Recreation, 2013)
Method of development it is referring to research development model of development of borg & amp; gall thathas been modified, namely: ( 1 ) did research and collecting information, preliminary including observationkajian lapangan and library. ( 2 ) developed the product. ( peraturan early form of football feet and hands ). ( 3)evaluation experts by using one expert penjas and his learning, small group, and trial by using a questionnaireand consultation and evaluation and analyzed. ( 4 ) the first revision products based on the revision of expertevaluation and trial smaii group ( 16 students ). Revision is used for product improvement tehadap early madeby researchers. ( 5 ) the trial lapangan ( 34 students ).( 6 ) revision the final product conducted based on the trialof the field. ( 7 ) the final result kind of classroom soccer bolamelalui football feet and hands for students class velementary produced through revision test lapangan.pengumpulan data conducted using a questionnaireobtained from expert evaluation ( one skilled penjas and one skilled learning ), test small group ( 16 studentspublic elementary beji 1 ), and trial of the field ( 34siswa class v public elementary beji 1 ) .data form of theassessment about quality products, Advice to repair products, and results charging a questionnaire bysiswa.teknik analysis of data used is descriptive percentage to uncover aspect psychomotor, cognitive, and andaffective students after using products.